Chinese and Chinese mestizos of Manila : family, identity, and culture, 1860s-1930s - Chu, Richard T. (Chinese overseas, 2010)
"Building on works in Chinese transnationalism and cultural anthropology, this book examines the everyday practices of Chinese merchant families in Manila from the 1860s to the 1930s. The result is a fascinating study of how families and individuals creatively negotiated their identities in ways that challenge our understanding of the genesis of ethnic identities in the Philippines."--Jacket